(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: Fixed-point theory is an important area of study in pure and applied mathematics, and it is a flourishing area of research in the paperwork, the concept of fuzzy S-metric space is introduced, and The fixed point theorem’s existence and uniqueness over fuzzy S-metric space are examined. We will go over The fixed point theorem’s existence and uniqueness for k contractive mapping in fuzzy S-metric space. These theorems will be seen in fuzzy S-metric space. fixed point theory The transcendence is the main cause of the fixed point theory’s recent resurgence. The significance of this theory and the questions it allows us to address regarding the dimensions of space. Proof of the existence of solutions to the physical equations is possible thanks to the notion of the fixed point. Materials and Methods: We will discuss the existence and uniqueness of the fixed point theorem by using k contractive mapping in fuzzy S-metric space. Results: This study proved the existence and uniqueness of new fixed point theorem in fuzzy S-metric space using k contractive mapping. Conclusions: According to this study, we were able to prove the existence and uniqueness of fixed points in s-metric space by using k-fuzzy contractive mapping.